ANALISIS MANAJEMEN INOVASI DALAM PENGEMBANGAN LAYANAN INDUSTRI KESEHATAN DIGITAL - Dewi, Mariana Puspa (JURSIMA, 2022)
The advancement of digital technology innovations has become a major driver of transformation across various companies, including in the healthcare sector. This technological development expands the scope of organizational management performance to ensure that the services provided by companies are maximized. This research analyzes innovation management in the development of digital healthcare services, identifies key factors influencing successful implementation, and provides recommendations for overcoming existing barriers using the ADKAR model (Awareness, Desire, Knowledge, Ability, Reinforcement). Using a qualitative approach, the study employs literature review, documentation, and observation to identify themes and patterns in the data. The results of the research indicate that Awareness of the benefits of digital technology is crucial and can be enhanced through clear and structured communication. Support from top management and communication of personal and professional benefits increase Desire for change among healthcare staff. Adequate Knowledge about the use of new technology can be achieved through comprehensive and ongoing training programs. The Ability to apply new technology in daily practice is essential and can be supported by practical exercises and responsive technical support. Reinforcement through continuous monitoring and provision of incentives helps to sustain the use of new technology. To achieve success in managing digital healthcare service innovation, organizations must increase Awareness through effective communication campaigns, enhance Desire with clear top management support, improve Knowledge through comprehensive training programs, boost Ability by providing practical exercises and technical support, and ensure Reinforcement through continuous monitoring and incentive provision.